Modeling of high frequency high voltage of waveforms on life of enamel insulation - S. Narasimha Rao; Elanseralathan Kasinathan (Institute of Advanced Engineering and Science, 2021)
In recent years it has been observed that insulation failure in electrical motors is caused by adjustable speed drives fed by power electronic converters. These converters produce impulse waveforms having a high slew rate generated by the high switching frequency of IGBTs. This paper focuses on high switching frequency stress in low voltage electrical motors for adjustable speeds. To examine the motor winding insulation under such stress twisted-pair samples were developed from enameled wires. A single-coated polyester of enamel with a thickness of 40 microns is used for this work. High-frequencies, high voltages of Square, and Square-rising, Square-spike waveforms of 10-30 kHz are used here. The test results show that the insulation fails earlier for the Square waveform compared to the Square-spike and Square-rising waveforms. In a nutshell, there is an analysis of PD formation in the insulation system at a higher switching frequency is analyzed. Electric field distributions between twisted pairs with various air gaps of the insulation system stressed by the Square and Square-rising waveforms up to 30 kHz are modeled using COMSOL software.